Legitimising EU Governance through Performance Assessment Instruments - Bartolomeo Cappellina (International Review of Public Policy)
The article addresses the production of indicators as policy instruments in European public policy. It discusses the relevant literature on sociology of quantification and European public policy and applies this theoretical framework to the case of European judicial administration policy. Presenting the historical and institutional premises to the creation of two projects of judicial performance assessment by the Council of Europe and the European Commission, as well as their methodology, the article argues that the selection of indicators is a litmus test of debates over the strategies and institutional goals of the organisations proposing them. Connecting the previous analysis with the use of these instruments in the policy-making sphere, the article points out that evaluation tools in European policy, rather than serving merely as informative tools, produce empowerment side-effects in the policy arena for the organisations that developed them. In European judicial policy, indicators provide a sufficiently loose framework to solve vertical and horizontal cooperation problems at the international level, determine policy goals through the selection of areas of measurement and evaluation, and provide proof to influence local and national policy-makers over reforms either through lesson-drawing, persuasion or conditionality.